Simulation Study on Internal Short Circuits in a Li-Ion Battery Depending on the Sizes, Quantities, and Locations of Li Dendrites - Kim, Suhwan; Song, Jihun; Lee, Hyobin; Jung, Seungwon; Park, Joonam; Lee, Hongkyung; Lee, Yong Min (Frontiers in Materials, 2022)
The internal short circuit caused by the Li dendrite is well known to be a major cause for fire or explosion accidents involving state-of-the-art lithium-ion batteries (LIBs). However, post-mortem analysis cannot identify the most probable cause, which is initially embedded in the cell, because the original structure of the cell totally collapses after the accident. Thus, multiphysics modeling and simulation must be an effective solution to investigate the effect of a specific cause in a variety of conditions. Herein, we reported an electrochemical-thermal model to simulate the internal short circuit depending on Li dendrite’s sizes (1, 3, 5, 7, and 9 μm), quantities (1–9), relative locations (0, 25, 50, 100, and 150 μm), and external temperature (−10, 10, 30, and 50°C). Through monitoring the temperature change affected by the joule and reaction heats for each case, we suggested critical conditions that led to unavoidable thermal runaway. Thus, this model can be a steppingstone in understanding the correlation between internal short circuits and Li dendrites.